The Influence of Environmental Sanitation on Stunting - Zahtamal, Zahtamal; Restila, Ridha; Sundari, Sundari; Palupi, Resti (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: According to Pekanbaru City Health Department in 2019, there were 17.,67% of toddlers in Pekanbaru with poor nutritional status. Poor sanitation can trigger the emergence of infectious diseases that can reduce nutritional absorption in toddlers throughout the digestive process, resulting in stunting. The aim of this study was to analyze environmental sanitation influences on stunting. Methods: This research used case control study design. The case and control groups each received 30 samples. Independent variables include water source for sanitation, condition of latrines, condition of hand washing facilities with soap, condition of waste water drainage channels, management of household waste, type and condition of floors, presence of vectors and disease carrier animals, drinking water quality from biological conditions. The dependent variable was stunting. All data were collected using questionnaires that were asked directly to participants. Data analysis was performed by using the chi-square and multiple logistic regression tests. Results and Discussion: Water sources for sanitation, availability and condition of latrines, drinking water quality from biological terms influences on stunting (p-value <0.,05). Multivariate tests show that, the drinking water quality from biological terms and water sources for sanitation had a probability value of 21% to cause stunting. Conclusion: The dominant factor influences on stunting is the drinking water quality in biological terms and water sources for sanitation.